2020
DOI: 10.1177/2150135120916744
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to Cardiac Xenotransplantation by Pediatric Heart Surgeons and Physicians

Abstract: Background: Cardiac transplantation in early childhood is limited by scarcity of organ donors. Advances in cardiac xenotransplantation (XTx) research suggest that xenografts may one day represent an alternative to allografts. We sought to determine the attitudes among surgeons and cardiologists in the field of pediatric cardiac transplantation toward the potential use of XTx if this clinical option were to become a reality. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
0
17
1
Order By: Relevance
“…While clinical considerations, including further immunological and safety‐related aspects of XTx, must be overcome, ethical and social aspects also need to be considered before clinical trials can be initiated. To date, there have been a number of quantitative survey‐based studies assessing attitudes of various persons toward XTx, with much of the research showing that potential acceptance of XTx is high 4‐7 . However, the use of qualitative methodology, which is designed to elicit viewpoints that may not be present in surveys, has been limited and not with a broad array of stakeholders 8 …”
Section: Introductionmentioning
confidence: 99%
“…While clinical considerations, including further immunological and safety‐related aspects of XTx, must be overcome, ethical and social aspects also need to be considered before clinical trials can be initiated. To date, there have been a number of quantitative survey‐based studies assessing attitudes of various persons toward XTx, with much of the research showing that potential acceptance of XTx is high 4‐7 . However, the use of qualitative methodology, which is designed to elicit viewpoints that may not be present in surveys, has been limited and not with a broad array of stakeholders 8 …”
Section: Introductionmentioning
confidence: 99%
“…Our interdisciplinary group has conducted multiple research surveys and focus groups to elicit the public's perception of pediatric cardiac and adult kidney xenotransplantation. [3][4][5] We have consulted numerous stakeholders, including religious leaders, organ procurement staff/administrators, healthcare providers who care for possible future candidates, patients themselves, parents of children who may need an organ or are transplant recipients, and local businesspersons. [3][4][5] In summary, these studies found little or no religious, ethical, or social concerns among these stakeholders, with considerable support for xenotransplantation given results are comparable to allotransplantation (which, of course, is not yet known).…”
mentioning
confidence: 99%
“…[3][4][5] We have consulted numerous stakeholders, including religious leaders, organ procurement staff/administrators, healthcare providers who care for possible future candidates, patients themselves, parents of children who may need an organ or are transplant recipients, and local businesspersons. [3][4][5] In summary, these studies found little or no religious, ethical, or social concerns among these stakeholders, with considerable support for xenotransplantation given results are comparable to allotransplantation (which, of course, is not yet known). There was also support for its use to bridge patients until a deceased human donor organ could be obtained, which is our suggested therapy for infants.…”
mentioning
confidence: 99%
“…Our interdisciplinary group has conducted multiple research surveys and focus groups to elicit the public's perception of pediatric cardiac and adult kidney xenotransplantation. [4][5][6] We have consulted numerous stakeholders, including religious leaders, organ procurement staff/administrators, healthcare providers who care for possible future candidates, patients themselves, parents of children who may need an organ or are transplant recipients, and local businesspersons. [4][5][6] In summary, these studies found little or no religious, ethical, or social concerns among these stakeholders, with considerable support for xenotransplantation given results are comparable to allotransplantation (which, of course, is not yet known).…”
mentioning
confidence: 99%